Agent-Based Models for Climate Change Adaptation in Coastal Zones. A Review - Jlenia Di Noia (Fondazione Eni Enrico Mattei (FEEM), 2022)
Worldwide, with different frequencies and magnitudes, coastlines are increasingly being affected by climate change hazards. The high urbanization rate, due to economic opportunities and natural amenities, further exacerbates vulnerabilities in these areas, requiring prompt and effective adaptation to climate induced events –from gradual sea level rise to abrupt storms and floods. The ability of different actors (households, firms, financial entities and Government) to cope with such events can be addressed and studied through the use of agent-based models, which allow for an heterogeneous treatment of agents' behaviour, from individual risk perceptions' modelling to decision-making rules on the adaptation option to be put into practice (whether related to coastal management or to coastal defense). Since the natural system needs to be considered together with the socio-economic human system, if we are willing to enhance sustainable practices, integrated-assessment models can be used as a tool to account for these interrelated complexities. A comprehensive review on integrated-assessment agentbased models on climate change adaptation in coastal zones, thus, is here provided to investigate the current state of the art.
Keywords: C63; Q01; Q26; Q54; 330; Agent-based models; Integrated-assessment models; Review; Climate change; Adaptation; Coastal zones